Study of Mechanical Strength Characteristics For Roller Compacted Concrete with Recycled Aggregates - ASAAD, MAJED; KHEIRBEK, ALI; IBRAHIM, ALI (Latakia University Journal -Engineering Sciences Series, 2020)
Recycled aggregates have globally proven to be extremely flexible to use in various engineering applications after they have previously been used exclusively for laying foundations in road works, backfilling and soil replacement for improvement, but the accelerated urban development that necessitated consumption of large quantities of aggregates has led specialists to find methods which aimed to take advantage of the huge quantities produced annually from demolition and construction waste and converted them to gravel that will form a reservist to natural ones for being used in various types of structural concrete, such as roller compacted concrete. This research focuses on producing compacted concrete using different proportions of recycled aggregates, and studying its mechanical strengths (Compressive Strength, Splitting Tensile Strength, Flexural Tensile Strength) to determine how they are affected by the replacement process. The research found that the use of recycled aggregates in producing of compacted concrete seems very positive. With a 50% replacement rate, achieved relatively higher compressive strength values, noting that the values that were expected to be low, as the splitting tensile strength and flexural tensile Strength, looked very good for this Type of concrete compared with that identical of concrete manufactured with natural aggregates. أثبتت الحصويّات المعاد تدويرها عالميّاً مرونةً كبيرة للاستعمال في مختلف التطبيقاتٍ الهندسيّة بعد أن اقتصر استعمالها سابقاً على طبقات التأسيس في الأعمال الطرقية، لكنّ التطّور العمراني المتسارع الذي استوجب استهلاك كميّات كبيرة من الحصويّات دفع المختصيّن إلى إيجاد منهجيّات تهدف للاستفادة من الكميّات الهائلة المنتجة سنويّاً من نفايات الهدم والإنشاء وتحويلها لحصويات تشكّل رديفاً للحصويّات الطبيعية بهدف استعمالها في مختلف أنواع البيتون الإنشائي كالبيتون المرصوص بالمداحي. يركّز هذا البحث على إنتاج بيتون مرصوص باستعمال نسبٍ مختلفةٍ من الحصويّات المعاد تدويرها، ودراسة مقاوماته الميكانيكيّة (المقاومة على الضغط البسيط، مقاومة الشد بالفلق، مقاومة الشد بالانعطاف) للوقوف على مدى تأثّرها بعمليّة الاستبدال. توصّل البحث إلى أنّ استخدام الحصويّات المعاد تدويرها في إنتاج البيتون المرصوص يبدو إيجابيّاً جدّاً، حيث حقّقت نسبة الاستبدال 50% قيماً أعلى نسبيّاً للمقاومة على الضغط البسيط مع الإشارة إلى أنّ القيم التي كان يتوقّع أن تكون منخفضةً كالمقاومة على الشد بالانعطاف والشدّ بالفلق بدت جيّدةً جدّاً لهذا النوع من البيتون مقارنةً مع مثيلاتها للبيتون المصنّع باستخدام حصويّاتٍ طبيعيّة.